IN THE ENGLISH LINGUOCULTURE THE CONCEPT OF "CHILD" AND THEIR MEANS - Ruzieva , Khayotkhon; Abdurakhmonov, Vohid (Евразийский журнал социальных наук, философии и культуры, 2022)
The study was carried out in line with the cognitive and culturological trends of modern linguoconceptology and is devoted to the analysis of the English concept «child». The object of the study is the concept of «child», verbalized in modern English. The subject of the study is the specificity of the objectification of the concept «child» by multi-level linguistic means. The main purpose of the article is to comprehensively describe the concept of «child» as a linguocultural and cognitive-pragmatic phenomenon relevant to the English national consciousness, by identifying and systematizing the ways of its linguistic representation in the English language picture of the world.